2016
DOI: 10.18045/zbefri.2016.2.529
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of financial development on growth: A time-varying causality analysis for Turkey

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This measure excludes credit to public sector and credit issued by the CBE and, thus, it measures the effectiveness of financial intermediaries in transferring savings to investors. Hence, it is more closely related with the impact of financial development on investment and economic development than other measures (Ak et al, 2016). Both variables are transformed into natural logarithms.…”
Section: Data Empirical Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This measure excludes credit to public sector and credit issued by the CBE and, thus, it measures the effectiveness of financial intermediaries in transferring savings to investors. Hence, it is more closely related with the impact of financial development on investment and economic development than other measures (Ak et al, 2016). Both variables are transformed into natural logarithms.…”
Section: Data Empirical Results and Discussionmentioning
confidence: 99%
“…This conclusion confirms to that of (Bolbol et al, 2005) who found that BBFD (measured as the ratio of private credit to GDP) had a positive influence on total factor productivity growth at higher levels of GDP per capita. Furthermore, Ak et al (2016) Moreover, the causality pattern showed a bidirectional relationship between banking sector development and stock market development and, thus, they were found to be complementary rather than substitutes in Egypt. To sum up and according to the survey conducted by (Nyasha & Odhiambo, 2014), the relationship between EG and BBFD varies depending on, inter alia, the proxy employed to measure the level of bank financial development; the level of development of the sample countries; data sets; and the methodology used.…”
Section: Bank-based Financial Development and Economic Growth: A Briementioning
confidence: 96%
See 3 more Smart Citations